Cereus sinensis Polysaccharide Alleviates Antibiotic-Associated Diarrhea Based on Modulating the Gut Microbiota in C57BL/6 Mice - Cui, Mingxiao; Wang, Yu; Elango, Jeevithan; Wu, Junwen; Liu, Kehai; Jin, Yinzhe (Frontiers in Nutrition, 2021)
The present study investigated whether the purified polysaccharide from Cereus sinensis (CSP-1) had beneficial effects on mice with antibiotic-associated diarrhea (AAD). The effects of CSP-1 on gut microbiota were evaluated by 16S rRNA high-throughput sequencing. Results showed that CSP-1 increased the diversity and richness of gut microbiota. CSP-1 enriched Phasecolarctobacterium, Bifidobacterium and reduced the abundance of Parabacteroides, Sutterella, Coprobacillus to near normal levels, modifying the gut microbial community. Microbial metabolites were further analyzed by gas chromatography-mass spectrometry (GC-MS). Results indicated CSP-1 promoted the production of various short-chain fatty acids (SCFAs) and significantly improved intestinal microflora dysfunction in AAD mice. In addition, enzyme linked immunosorbent assay and hematoxylin-eosin staining were used to assess the effects of CSP-1 on cytokine levels and intestinal tissue in AAD mice. Results demonstrated that CSP-1 inhibited the secretion of interleukin-2 (IL-2), interleukin-1β (IL-1β) and tumor necrosis factor-α (TNF-α) and improved the intestinal barrier. Correspondingly, the daily records also showed that CSP-1 promoted recovery of diarrhea status score, water intake and body weight in mice with AAD. In short, CSP-1 helped alleviate AAD by regulating the inflammatory cytokines, altering the composition and richness of intestinal flora, promoting the production of SCFAs, improving the intestinal barrier as well as reversing the dysregulated microbiota function.